ind Lupu Lumai : Komunikasi Kekerabatan Masyarakat Negeri Mamala - Fitriyani, Andi; Putuhena, M. Ihwan F.; Iftiya Salwa (IAIN Ambon, 2024)
This researsch seeks to determine the kinship communication process of the Mamala people in the lupu lumai tradition and the role of the lupu lumai tradition in the kinship communication.The research method used in this study is the ethnographic approach to communication, namely the application of ethnographic methods to patterns or ways of interacting and / or communicating in every event or communication process in community groups.The results of this study show that the process of kinship communication in the Lupu Lumai tradition takes place for generations, and is an association between families. Then this process is carried out through the stages of communication, namely, first; The Lupu Lumai event began with traditional elders ordering marinyo from traditional institutions to perform pasoa by beating gongs, tifa tahuri so that the community immediately gathered. Second: say greetings from the informers to the recipients of information. In addition, Lupu Lumai is an ancestral tradition that symbolizes each clan in Mamala Country to form unity and solidarity among the community. The role of Lupu Lumai as a kinship system of the people of Mamala has the function of attachment in fostering social relations. for example, Lupu Lumai, in the marriage tradition, if a family that has a lack of consumptive needs, then the role of other families is to help ease the burden. Furthermore, the role of the Lupu Lumai kinship system can strengthen the integrity of the local community. Strong ties in the kererabatan system should affect the inclusive attitudes of ethnic groups, customs and culture.